Quantitative brain morphometry identifies cerebellar, cortical, and subcortical gray and white matter atrophy in late-onset Tay-Sachs disease - Májovská, Jitka; Nestrašil, Igor; Ahmed, Alia; Bondy, Monica T; Klempíř, Jiří; Jahnová, Helena; Schneider, Susanne A; Horáková, Dana; Krásenský, Jan; Ješina, Pavel; Vaneckova, Manuela; Nascene, David R; et al. (Journal of inherited metabolic disease, 2024)
Cerebellar atrophy is a characteristic sign of late-onset Tay-Sachs disease (LOTS). Other structural neuroimaging abnormalities are inconsistently reported. Our study aimed to perform a detailed whole-brain analysis and quantitatively characterize morphometric changes in LOTS patients. Fourteen patients (8 M/6F) with LOTS from three centers were included in this retrospective study. For morphometric brain analyses, we used deformation-based morphometry, voxel-based morphometry, surface-based morphometry, and spatially unbiased cerebellar atlas template. The quantitative whole-brain morphometric analysis confirmed the finding of profound pontocerebellar atrophy with most affected cerebellar lobules V and VI in LOTS patients. Additionally, the atrophy of structures mainly involved in motor control, including bilateral ventral and lateral thalamic nuclei, primary motor and sensory cortex, supplementary motor area, and white matter regions containing corticospinal tract, was present. The atrophy of the right amygdala, hippocampus, and regions of occipital, parietal and temporal white matter was also observed in LOTS patients in contrast with controls (p < 0.05, FWE corrected). Patients with dysarthria and those initially presenting with ataxia had more severe cerebellar atrophy. Our results show predominant impairment of cerebellar regions responsible for speech and hand motor function in LOTS patients. Widespread morphological changes of motor cortical and subcortical regions and tracts in white matter indicate abnormalities in central motor circuits likely coresponsible for impaired speech and motor function.
Keywords: atrofie; bílá hmota; White Matter; Magnetic Resonance Imaging; retrospektivní studie; magnetická rezonanční tomografie; mozek; Tay-Sachs Disease; Humans; late-onset Tay-Sachs disease; GM2-gangliosidosis; lidé; Tay-Sachsova nemoc; Retrospective Studies; MRI; Brain; Atrophy; brain atrophy